Pengaruh Penambahan Tepung Kulit Ari Kedelai terhadap Pertumbuhan Burung Puyuh (Cortunix-cortunix japonica) - Isnaeni Karunia Annisa; Siti Harnina Bintari; Pramesti Dewi; Dewi Mustikaningtyas (Universitas Negeri Semarang, 2023)
Soybean hulls is a solid waste from the tempe industry. Utilization of soybean epidermis has not been done optimally. Soybean hulls contains isoflavone compounds and crude protein which are expected to be utilized in quail feed. This study aims to examine the effect of feeding with soybean hulls at different concentrations on the growth of quail. The research was conducted using a completely randomized design (CRD) with 4 treatments and 8 replications. The research material used 32 laying quails aged 42 days. Feed treatment with the addition of soybean epidermis consisted of P0 (without soybean hulls), P1 (7.5% addition of soybean hulls), P2 (10.5% addition of soybean hulls), and P3 (13.5% addition of soybean hulls). Parameters observed consisted of feed consumption, body weight gain, and feed conversion. The research data were analyzed using ANOVA, if it had a significant effect it was continued with the BNJ test (5%). The results of the analysis of variance showed that the addition of soybean hulls had a significant effect on feed consumption and body weight gain, but had no significant effect on feed conversion. It can be concluded that the addition of soybean husk as much as 7.5% is still effective in increasing weekly feed consumption and is able to provide the best feed conversion value.